2022
DOI: 10.1186/s12903-022-02256-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates and treatment needs of dental caries among people on antiretroviral therapy in Uganda: a cross sectional study

Abstract: Background Oral diseases are estimated to affect half of people living with HIV in the western world, and are often marked by pain, discomfort, disfigurement and reduced quality of life. Both HIV-specific and antiretroviral therapy-associated oral diseases have been found in this population. However, the prevalence, correlates and treatment needs of dental caries among people on antiretroviral therapy has not been well studied in rural Africa where majority of people living with HIV reside. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Urban residents defined a city, municipality, gazetted town board or a trading center while rural residence [ 17 ]. The questionnaire was administered by a trained research assistant and the dental examination chart was completed by a single well trained dental surgeon with over 20 years’ experience [ 18 ]. After completion of the questionnaire, participants were directed to the dental surgeon for a dental examination, as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Urban residents defined a city, municipality, gazetted town board or a trading center while rural residence [ 17 ]. The questionnaire was administered by a trained research assistant and the dental examination chart was completed by a single well trained dental surgeon with over 20 years’ experience [ 18 ]. After completion of the questionnaire, participants were directed to the dental surgeon for a dental examination, as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire had ve major sections: socio-demographic factors, diabetes history, oral health status, dental health care (brushing, dental checkup habits, and use of toothpaste), dietary factors (i.e., consumption of fresh fruits, sugary foods), lifestyle factors (tobacco and alcohol use) and dental examination guided the modi ed World Health Organization (WHO) oral health questionnaire for adults [8]. The questionnaire was administered by a trained research assistant and the dental examination chart was completed by a single well trained dental surgeon [9]. After completion of the questionnaire, participants were directed to the dental surgeon for a dental examination, as previously described [9].…”
Section: Data Collectionmentioning
confidence: 99%
“…The questionnaire was administered by a trained research assistant and the dental examination chart was completed by a single well trained dental surgeon [9]. After completion of the questionnaire, participants were directed to the dental surgeon for a dental examination, as previously described [9]. Disposable dental mirrors and probes under natural light to examine the participant while seated in a reclined position were used.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study done in Uganda, reported a caries prevalence of 80% in adolescents living with HIV taking ART compared to 67% in the general adult population (17). Another study carried out in Uganda reported that individuals living HIV and taking ART had a need of dental treatment of about 96% and a DMFT (Decayed, Missing, Filled Teeth) score of four (14). People living with HIV (PLHIV) are now living longer due to ART, which means that oral diseases, such as dental caries and other oral manifestations are increasingly important to manage in this population.…”
Section: Introductionmentioning
confidence: 99%